Respuesta :
- y=x³
Horizontally streched means change in x
So
New equation
- y=kx³
k is factor
- y=1/5x³
We know the rule for reflection (x,y)=(x,-y)
So
New function
- -y=1/5x³
- y=-1/5x³
Option D
![Ver imagen Аноним](https://us-static.z-dn.net/files/dfd/01efa2e81c77dd03ee0d498d532f38c1.jpg)
Step-by-step explanation:
The graph of y = √x is reflected in the y-axis, is horizontally stretched by a factor of 2, shifted 3 units up and 1 unit left. What is the equation of the transformed graph?
Original: y = √(x)
Reflected in the y-axis: y = √(-x)
Horizontally stretched by a factor of 2: y = √(-x/2)
Shifted 3 units up: y = 3 + √(-x/2)
And 1 unit left: y = 3 + √(-(x+1)/2)